English Enhancing Exercises: An effective strategy to upgrade and enhance the English proficiency of medical students in non-English speaking countries - Zubairi, Nadeem Alam (Pakistan journal of medical sciences, 2025)
English as a medium of Instruction (EMI) has been adopted by the majority of non-native English-speaking countries for teaching science subjects. Medicine is no exception. The decision is based on enormous associated advantages both during the undergraduate period and in professional life as a doctor. However, the linguistic barrier does impose numerous deficiencies related to proficiency in English. This, if not corrected, leads to suboptimal learning and affects the career and output. Formal and dense measures have been suggested but are against the cognitive load on a medical student. English Enhancing Exercises (EEE) is an easy-to-do student-friendly approach, that gradually and spirally helps out without any additional burden. doi: https://doi.org/10.12669/pjms.41.7.12632 How to cite this: Zubairi NA. English Enhancing Exercises: An effective strategy to upgrade and enhance the English proficiency of medical students in non-English speaking countries. Pak J Med Sci. 2025;41(7):2152-2155. doi: https://doi.org/10.12669/pjms.41.7.12632 This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.